Manifesto for Digital Social Touch in Crisis - Jewitt, Carey; Price, Sara; Steimle, Jürgen; Huisman, Gijs; Golmohammadi, Lili; Pourjafarian, Narges; Frier, William; Howard, Thomas; Ipakchian Askari, Sima; Ornati, Michela; Panëels, Sabrina; Weda, Judith (Frontiers in Computer Science, 2021)
This paper presents a Manifesto for Digital Social Touch in Crisis - a provocative call to action to designers, developers and researchers to rethink and reimagine touch through a deeper engagement with the social and sensory aspects of touch. The paper situates the manifesto in the key challenges facing designers and developers through a discussion of the state-of-the-art of research on haptics. The features and purpose of the manifesto form are described, along with our rationale for its use. The method of the manifesto development is outlined, this involved a series of interdisciplinary collaborative workshops with participants from computer science, design, engineering, HCI and social science from both within industry and academia. The starting points, opportunities and challenges, dominant themes and tensions that shaped the manifesto statements are then elaborated on. The paper shows the potential of the manifesto form to bridge between HCI, computer science and engineers, and social scientists on the topic of social touch.